2023
DOI: 10.1002/cam4.5783
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world treatment and outcomes of patients with metastatic BRAF mutant colorectal cancer

Abstract: Background BRAF mutation occurs in 5%–10% of metastatic colorectal cancers (mCRCs). Patients with BRAF mutant mCRC exhibit a specific metastatic pattern and poor prognosis. Survival outcomes are heterogeneous in cases of mCRC with a BRAF mutation. The optimal first‐line therapy is still controversial. Methods We retrospectively reviewed the medical records of patients with mCRC between June 2010 and December 2021. Clinicopathologic characteristics, treatment and BRAF mutation testing results were collected. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Accompanying a greater awareness of the genetic drivers of tumor biology, there is speculation regarding the potential correlation between certain molecular cancer biomarkers, such as ras and braf, and the incidence and prognostic implications of CRLM ( 40 ). The occurrence of KRAS mutations among CRC exceeds 50%, whereas the occurrence of HRAS and NRAS mutations is rather infrequent ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accompanying a greater awareness of the genetic drivers of tumor biology, there is speculation regarding the potential correlation between certain molecular cancer biomarkers, such as ras and braf, and the incidence and prognostic implications of CRLM ( 40 ). The occurrence of KRAS mutations among CRC exceeds 50%, whereas the occurrence of HRAS and NRAS mutations is rather infrequent ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted in China has revealed contrasting clinical characteristics between Chinese and Western patients with BRAF mutations in metastatic CRC. These disparities mostly emerge as an earlier beginning age and a reduced occurrence of microsatellite instability among Chinese patients ( 40 ). In a multicenter retrospective study conducted in China, it was observed that BRAF V600E, the most common kind of BRAF mutation, is the key factor impacting OS in patients with CRLM ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…This specific SNP mutation is tumorigenic to human cells by disrupting the normal growth cycle and interfering with extracellular signaling pathways. Therefore, the BRAF V600E mutation is often regarded as a biomarker of aggressive tumor growth in different cancers, such as metastatic melanoma, papillary thyroid cancer, and colorectal cancer. , …”
mentioning
confidence: 99%
“…Therefore, the BRAF V600E mutation is often regarded as a biomarker of aggressive tumor growth in different cancers, such as metastatic melanoma, papillary thyroid cancer, and colorectal cancer. 3,4 Due to its exceptional programmability and high sensitivity, the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) system has attracted much attention in recent years. 5 The type V CRISPR system (including Cas12a, Cas12b, Cas12f, etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation